Manoeuvring speed estimation of a lane-change system using geometric hermite interpolation - N.A. Othman; U. Reif; A. Ramli; M.Y. Misro (Ain Shams Engineering Journal, 2021)
Autonomous vehicles demand a continuous path to provide the passengers with physical ease and relaxation. Smooth experience in autonomous vehicles is very essential and can be accomplished by having good trajectories. The trajectory generated by the interpolation algorithm for Geometric Hermite is provided in this paper. The proposed algorithm calculates a path based on a set of geometric Hermite data that consists of predefined points including prescribed tangent angles and curvature values. The generated path has the potential to determine the maximum speed allowed for safe autonomous driving on roads by providing curvature information. It describes an alternative way to estimate design speed permitted on the road for autonomous lane change systems.